(untitled) (The Lumbini Journal of Business and Economics, 2024)
It is with great pride and pleasure that we present the latest edition of The Lumbini Journal of Business and Economics, Volume XII, No. 1. This issue reflects the tireless dedication and collaborative efforts of researchers, reviewers, and the entire editorial team, all of whom have worked rigorously to uphold the quality and relevance of research within this publication. As the Research and Development Department of Lumbini Banijya Campus (LBC) continues its commitment to fostering academic excellence, this journal serves as a vital platform for scholars to disseminate their work. It’s hoped that this issue not only adds value to the academic community but also inspires future research endeavors in the business and economic spheres of Nepal. The editorial team deeply grateful to the distinguished contributors who have provided their research and insights, adding a diverse array of perspectives to the journal. Their valuable contributions have been instrumental in shaping this edition. I also extend my heartfelt thanks to the editorial board, peer reviewers, and the supportive faculty, staff, and students of LBC. Special acknowledgment is due to Mr. Surendra Prasad Shrestha, President of the Campus Management Committee, and Prof. Dr. Tara Prasad Upadhaya, Campus Chief, for their unwavering support in bringing this issue to completion. This edition comprises twelve research papers, covering a wide range of topics that are timely and relevant to the Nepalese economic landscape. While we have strived to ensure the highest quality and accuracy, we welcome feedback from our readers to guide us toward continual improvement in future publications. On behalf of the entire editorial team, I extend my deepest appreciation to all who have contributed to this issue. It is through such collective effort that we continue to uplift the standards of academic research in this region. I hope this journal enriches your understanding and inspires continued dialogue and exploration in the fields of business and economics.